2021
DOI: 10.1002/cpe.6541
|View full text |Cite
|
Sign up to set email alerts
|

Three‐class brain tumor classification from magnetic resonance images using separable convolution based neural network

Abstract: Summary Brain cancer is one of the deadliest hazards in the world and hence tumor classification became a dominant task in brain tumor diagnosis. There is a wide range of brain tumors, and each tumor exhibits distinct properties like location, shape, size, and texture. Thus, multi‐class brain magnetic resonance (MR) image classification became a trivial task. In this article, we have proposed a seven‐layer convolutional neural network to address three‐class brain MR image classification. We have employed separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…332 (259 HGG, 73 LGG), 2. 259 Normal x x x x Affine Khazaee et al [ 133 ] 2022 BraTS2019 ceT 1 w, T 2 w, FLAIR 335 (259 HGG, 76 LGG) 26,904 (13,233 HGG, 13,671 LGG) x x Isunuri et al [ 134 ] 2022 Figshare (Cheng et al, 2017) ceT 1 w 233 (as shown in Table 2 ) 3064 (as shown in Table 2 ) x x ...…”
Section: Resultsmentioning
confidence: 99%
“…332 (259 HGG, 73 LGG), 2. 259 Normal x x x x Affine Khazaee et al [ 133 ] 2022 BraTS2019 ceT 1 w, T 2 w, FLAIR 335 (259 HGG, 76 LGG) 26,904 (13,233 HGG, 13,671 LGG) x x Isunuri et al [ 134 ] 2022 Figshare (Cheng et al, 2017) ceT 1 w 233 (as shown in Table 2 ) 3064 (as shown in Table 2 ) x x ...…”
Section: Resultsmentioning
confidence: 99%
“…For the two datasets, the suggested method has accuracy of 99.8% and 97.14%. A seven-layer CNN was suggested in [110] to assist with the three-class categorization of brain MR images. To decrease computing time, separable convolution was used.…”
Section: Mri Brain Tumor Classification Using DLmentioning
confidence: 99%
“…A seven-layer CNN was suggested in [ 111 ] to assist with the three-class categorization of brain MR images. To decrease computing time, separable convolution was used.…”
Section: Literature Reviewmentioning
confidence: 99%